Correlação entre padrões cefalométricos craniofaciais e dimensões das vias aéreas faríngeas em adolescentes - OLIVEIRA, Izabel Cristina Vieira de (2018)
Evidences show that the functions of the oropharyngeal complex contribute to the development of craniofacial morphology and optimal occlusion. Thus, a morphological evaluation of the upper airways represents a fundamental procedure for the diagnosis, planning and orthodontic treatment follow up. Lateral cephalometric radiography is an inexpensive and reliable model for the evaluation of these structures. The objective of this dissertation was to analyze the relation between pharyngeal airway dimensions, sex, age and craniofacial factors, besides the investigation of degrees of correlation between the continuous measures. A cross-sectional study was carried out with a sample of 108 adolescents (54 males and 54 females) aged 12 to 18 years. Data and image exams were collected at a radiology center in the city of São Luís, MA, Brazil. The cephalometric tracings were performed by a single examiner previously trainer, obtaining a minimum concordance coefficient of 0.744 for the continuous measurements evaluated. Transversal measurements of the maxilla and mandible were evaluated through occlusal photographs. The SPSS 18.0 software was used in statistical analysis. Significance level adopted was 5%. In Chapter 1, it was an increase in the tongue's measure in men (P = 0.026); approximation of the jaw hyoid among men (P = 0.016), and jaw hyoid detachment among women (P = 0.039); increase in soft palate measurements (P = 0.003 and P = 0.007) and tongue (P = 0.018) in adolescents with anterior crossbite. The attitudes that make the difference between the genders and during the puberty process do not refer to the soft palate, the position of the hyoid bone and tongue. In Chapter 2, response levels of maxillary measurement, relation of the lower incisor to the base of the skull, lower facial height, relationship between the incisors, palate morphology and the tongue were modified for the purpose of differentiating from the airway pharyngeal according to the gender. These findings suggest that craniofacial and dental measurements are related to the dimensions of the pharyngeal airways, providing information for orthodontic diagnosis and planning.